PERLINDUNGAN HUKUM TERHADAP KREDITUR DALAM PEMBERIAN KREDIT DENGAN JAMINAN PURCHASING ORDER APABILA DEBITUR WANPRESTASI (STUDI PERJANJIAN KREDIT PT. BANK MANDIRI DENGAN PT. ERA BANGUN JAYA) - TAHI HERMAN ORBERT MANURUNG (PREMISE LAW JURNAL, 2017)
Basically, the economic growth which is closely related to public welfare does need the role of business world that is generally constrained by capital or funding. In terms of the world of business, funding constraint is the difficulty faced by the business practitioners, especially those are constrained by inadequate capital, to be able to access funding facility or credit provided by the banks and other financial institutions. To meet that need, recently the banks provided credit facility by accepting Purchasing Order as the collateral for the credit extended. Credit with Purchasing Order as the collateral can be taken by the bank as the consideration in extending the credit to the debtor supported by the analysis of the good-will and ability of the customer (debtor) in repaying the credit in accordance with what has been agreed. In addition, the bank can also anticipate all the risks which may occur through risk mitigation and the involvement of the credit guarantee insurance company to settle the risk in case the debtor breaches the agreement.Keywords: Purchasing Order, Risk Mitigation, Credit Agreement